ANALISIS KINERJA INDUSTRI TEPUNG KELAPA PT. ROYAL COCONUT KELURAHAN SARONGSONG SATU KECAMATAN AIRMADIDI KABUPATEN MINAHASA UTARA - Margareta Risa Doppo; Tommy F. Lolowang; Lorraine W. Th. Sondak (Sam Ratulangi University, 2017)
This study aims to determine the Performance of Coconut Flour Industry in Kelurahan Sarongsong Satu, Kecamatan Airmadidi, Minahasa Utara Regency reviewed from Balanced Scorecard is a financial perspective, customer perspective, internal business process perspective and learning and growth perspective. This research was conducted at PT. Royal Coconut located in Kelurahan Sarongsong Satu Kecamatan Airmadidi Minahasa Utara Regency. This research will be conducted for 3 months from preparation until preparation of report, that is from February until month Mey 2017. Sources of data taken in this research are primary data and secondary data. Primary data is data that comes from the observation (observation) and interview (interview) with the leadership and a number of company employees. Secondary data is data obtained in the form of reports from other information sourced from literature and other information related to this writing. The method of analysis used in this research is Balanced Scorecard method that is financial perspective, customer perspective, internal business process perspective and learning and growth perspective. This research found that performance of Coconut Flour Industry PT. Royal Coconut Kelurahan Sarongsong One District Airmadidi Minahasa Utara Regency reviewed from Balanced Scorecad that financial perspective can be measured well and perfect for getting a profit every month.